Sulfonated Tetraphenylethylene-Based Hypercrosslinked Polymer as a Heterogeneous Catalyst for the Synthesis of Symmetrical Triarylmethanes via a Dual C–C Bond-Cleaving Path - Kalita, Gitumoni; Deka, Namrata; Paul, Dipankar; Thapa, Loknath; Dutta, Gitish K.; Chatterjee, Paresh Nath (Synlett, 2020)
A sulfonic acid functionalized tetraphenylethylene-based hypercrosslinked polymer (THP-SO3H) with a well-developed porous network and accessible sulfonic acid sites was synthesized and characterized by different analytical techniques. The catalytic prowess of the synthesized material THP-SO3H was investigated in a challenging dual C–C bond-breaking reaction for the synthesis of symmetrical triarylmethanes (TRAMs) in high yield. The scope of the developed metal-free method was also explored with a wide variety of substrates. The organocatalyst can be easily recovered by filtration and reused up to five consecutive cycles without substantial loss in its catalytic efficacy.
Keywords: hypercrosslinked polymer; heterogeneous catalyst; reusable; C–C bond breaking; triarylmethane